Adhesive resin as well as preparation method and application thereof

Through the combination of the new adhesive resin and aramid fiber aerogel film, the mechanical properties of aramid fiber aerogel are improved, the problem of insufficient mechanical and mechanical properties is solved, and higher tensile strength and breaking extension are achieved The long-term rate has expanded its application prospects in the fields of thermal insulation, thermal insulation and sound insulation.

CN119285840AActive Publication Date: 2025-01-10CHONGQING UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411616503.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-10
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The mechanical and mechanical properties of aramid fiber aerogel films are limited in large-scale applications.

Method used

Using a new type of adhesive resin, N-hydroxymethylacrylamide, N,N-dimethacrylamide, methyl methacrylate, N,N-diethylaminoethyl methacrylate, propylene glycol mono Polymerization of components such as methyl ether and azodivaleronitrile, a binder resin with a molecular weight between 30,000 and 70,000 was prepared, and prepared by solution radical polymerization, and then combined with aramid fiber aerogel film. , after freeze-drying and heat cross-linking treatment, the aramid fiber aerogel film is modified.

Benefits of technology

The bending resistance and mechanical properties of aramid fiber aerogel are improved. The specific tensile strength of the modified aramid fiber aerogel film is increased by 22.22%-33.33%, and the elongation of the break is increased by 1.15%-28.74%. Low density and controllable, suitable for thermal insulation, thermal insulation and sound insulation in buildings, automobiles and home appliances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285840A_ABST
    Figure CN119285840A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of chemical materials, and relates to adhesive resin as well as a preparation method and application thereof. The adhesive resin is prepared by polymerizing monomers such as N, N-dimethylacrylamide, methyl methacrylate, methacrylic acid N, N-diethylaminoethyl ester, N-hydroxymethyl acrylamide and the like according to a specific proportion. The resin is used for preparing a modified aramid fiber aerogel film, and the specific tensile strength and the specific elongation at break of the film are remarkably improved through the steps of resin addition, acid treatment, neutralization, freeze drying, thermal crosslinking and the like. The invention solves the problem of poor mechanical properties of the existing aramid fiber aerogel film, provides an efficient, simple and convenient modification method, and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical materials and relates to adhesive resin and its preparation method and application Background Art

[0002] The full name of aramid fiber is polyphenylene phthalate, which is a high-performance fiber material with high modulus, high temperature resistance, corrosion resistance, low relative density, high strength and good insulation. Aramid fiber is a synthetic aromatic polyamide fiber, which is a synthetic linear polymer composed of aromatic rings (Ar-CONH-Ar) connected by amide bonds (at least 85% of the amide bonds are directly connected to 2 aromatic rings). The main chain is composed of aromatic rings and amide bonds. The aromatic ring structure is highly rigid, and the polymer chain is stretched to form a rod-like structure; at the same time, the linear molecular chain makes the aramid fiber space utilization rate high, so the unit volume can accommodate more polymers and therefore has higher strength. Different from ordinary flexible polymer molecular chains, the main chain structure of para-aramid fiber is mainly composed of a rod-like molecular structure formed by the para-position of benzene rings. Due to the presence of large conjugated benzene rings, it is difficult for the molecular chain segments to rotate internally, thus presenting a linear rigid structure. There are four main types of aramid fibers according to their molecular structure: poly(p-phenylene terephthalamide) (PPTA), isophthalamide (PMIA), heterocyclic aromatic polyamide fibers containing heteroatoms, and ortho-aramid fully aromatic polyamide fibers. PPTA and PMIA are the most widely used. They are widely used in military, aerospace, electronics, transportation, construction, medical and other fields.

[0003] Aramid fiber aerogel film has excellent insulation, heat insulation, corrosion resistance, heat insulation, flame retardancy, heat preservation and noise reduction properties. At the same time, compared with inorganic silica aerogel materials, aramid fiber aerogel film materials have better toughness and are not easy to break and produce powder particles under impact. However, the mechanical properties of aramid fiber aerogel film materials still limit their large-scale application, and how to modify and improve their mechanical properties is a difficult problem faced by this field. Therefore, the present invention prepares a new type of adhesive that is green, environmentally friendly, has good bonding strength, and has stable properties for the production of aramid fiber aerogel films, and improves the problems of low mechanical properties of aramid fiber aerogel films, which will have broad application prospects. Summary of the invention

[0004] In view of this, an object of the present invention is to provide an adhesive resin and a preparation method thereof, and an aramid fiber aerogel film prepared using the adhesive resin and a preparation method thereof.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides an adhesive resin, the chemical structural formula of the adhesive resin is as follows:

[0007]

[0008] Wherein x is the degree of polymerization of N,N-dimethylacrylamide, which is 31-78; y is the degree of polymerization of methyl methacrylate, which is 28-149; z is the degree of polymerization of N,N-diethylaminoethyl methacrylate, which is 68-179; m is the degree of polymerization of N-hydroxymethylacrylamide, which is 53-155;

[0009] The molecular weight of the adhesive resin is 30000-70000,

[0010] The molecular weight of the adhesive resin is preferably 40,000-50,000.

[0011] The adhesive resin is formulated in the following proportions by mass: 3.2% to 8.1% N-hydroxymethyl acrylamide, 2.5% to 5.8% N,N-dimethyl acrylamide, 13.3% to 16.6% methyl methacrylate, 6.5% to 8.1% N,N-diethylaminoethyl methacrylate, 62.7% propylene glycol monomethyl ether, 4.9% N,N-dimethylformamide, and 0.25% azobisisovaleronitrile (AIBN), with a solid content of 32.26%.

[0012] Furthermore, the preparation method of the adhesive resin comprises the following steps:

[0013] S1: Raw material preparation: N-hydroxymethyl acrylamide 3.2%-8.1%, N,N-dimethyl acrylamide 2.5%-5.8%, methyl methacrylate 13.3%-16.6%, N,N-diethylaminoethyl methacrylate 6.5%-8.1%,

[0014] S2: AIBN was used as the initiator and prepared into a 5% N,N-dimethylformamide solution.

[0015] S3: adding the raw materials in step S1 and the initiator solution in step 2 into a reactor containing a solvent in four times at intervals of 10 to 15 minutes, with a reaction temperature of 70-90°C, a reaction time of 5-10 hours, a stirring speed of 300 rpm to 450 rpm, and obtaining the adhesive resin by solution free radical polymerization.

[0016] The solvent is a mixed solution of propylene glycol monomethyl ether and N,N-dimethylformamide, and the composition formula of the solvent solution is as follows: 46.4% to 92.7% of propylene glycol monomethyl ether and 7.3% to 53.6% of dimethylformamide in weight percentage.

[0017] Furthermore, the adhesive resin is used to prepare a modified aramid fiber aerogel film.

[0018] The preparation method of the modified aramid fiber aerogel film comprises the following steps: directly adding the adhesive resin into an aramid fiber dispersion at 15.5% of the mass of the aramid fiber, then adding dilute hydrochloric acid or dilute sulfuric acid and stirring for 10-15 minutes to fully dissolve the polymer, then adding sodium carbonate solution or sodium hydroxide solution to neutralize the acid, and then the polymer is uniformly precipitated, and after being filtered and frozen for 8 hours, and then freeze-dried for 24 hours, it is thermally cross-linked in an oven at 100° C. for 4 hours to obtain the modified aramid fiber aerogel film.

[0019] The beneficial effects of the present invention are as follows: the obtained modified aramid fiber aerogel not only has the excellent properties of traditional aramid fiber aerogel, such as insulation performance, heat insulation performance, corrosion resistance, etc., but also improves the bending resistance and mechanical properties of the aramid fiber aerogel, and the specific tensile strength of the modified aramid fiber aerogel film is increased by 22.22%-33.33%, and the specific elongation at break is increased by 1.15%-28.74%. The modified aramid fiber aerogel film prepared by the method has low and controllable density, and has broad application prospects in the fields of heat preservation, heat insulation and sound insulation of buildings, automobiles and household appliances.

[0020] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0022] Figure 1 is the stress-strain curve of Example 1;

[0023] Figure 2 is the stress-strain curve of Example 2;

[0024] Figure 3 is the stress-strain curve of Example 3;

[0025] Figure 4 is the stress-strain curve of Example 4;

[0026] Figure 5 This is a picture of the adhesive resin solution for the aramid fiber aerogel film of Example 1;

[0027] Figure 6This is a picture of freeze drying of the modified aramid fiber aerogel in Example 1 in a freeze dryer;

[0028] Figure 7 This is a picture of the modified aramid fiber aerogel of Example 1 being thermally cross-linked in an oven;

[0029] Figure 8 This is a picture of the modified aramid fiber aerogel after thermal crosslinking in Example 1. DETAILED DESCRIPTION

[0030] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.

[0031] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.

[0032] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "front", "rear", etc. indicate the orientation or position relationship, they are based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as limiting the present invention. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0033] Example 1

[0034] First, weigh 1 g of N-hydroxymethyl acrylamide, 1.8 g of N,N-dimethyl acrylamide, 5.12 g of methyl methacrylate, 2 g of N,N-diethylaminoethyl methacrylate, and 19.4 g of propylene glycol monomethyl ether, and prepare 1.6 g of 5% by mass azobisisovaleronitrile (AIBN) dimethylformamide solution as an initiator, and react at 90°C for 4 hours to obtain an adhesive resin for aramid fiber aerogel film.

[0035] Aramid fiber aerogel film

[0036] The raw materials, dosage and preparation method of the aramid fiber dispersion are as follows: first weigh 10g of poly(p-phenylene terephthalamide) precursor, add 50g of deionized water to fully soak it, and then disperse it dropwise in 250g of deionized water under the action of a high shear homogenizing and dispersing emulsifier, and disperse it for 4h to obtain an aramid fiber dispersion.

[0037] Then, 1.55 g of the adhesive resin for the aramid fiber aerogel film was added to 310 g of the aramid fiber dispersion, and then 7 g of 9.8% by mass dilute sulfuric acid was added and stirred for 10-15 min, and then 10.9 g of 5% by mass sodium hydroxide solution was added and stirred for 10-15 min. 50 g of the mixed dispersion was taken, filtered and placed in the freezer of a refrigerator for 8 hours, and then freeze-dried for 24 hours, and then thermally cross-linked in an oven at 100°C for 4 hours to obtain a modified aramid fiber aerogel film product.

[0038] Performance Testing

[0039] The modified aramid fiber aerogel film product prepared above was cut into 10mm×50mm strips, and the strip thickness was measured using a vernier caliper, and its mass was measured using an analytical balance to calculate its density. The strips were then placed on an electronic universal testing machine for testing, and the tensile strength and elongation at break were recorded. The tensile strength and elongation at break were divided by the density to obtain the specific tensile strength (MPa·cm 3 / g) and specific elongation at break (%·cm 3 / g). Figure 1 The tensile strength of the sample is 0.949 MPa, the elongation at break is 4.10%, and the specific tensile strength and specific elongation at break are 0.022 MPa·cm 3 / g, 0.094%·cm3 / g. At the same density, its tensile strength and toughness are better than those of unmodified aramid fiber aerogel film.

[0040] Example 2

[0041] The raw materials, dosage and preparation method of the adhesive for preparing aramid fiber aerogel film in this embodiment are as follows: first, weigh 2 g of N-hydroxymethyl acrylamide, 1 g of N,N-dimethyl acrylamide, 4.42 g of methyl methacrylate, 2.5 g of N,N-diethylaminoethyl methacrylate, and 19.4 g of propylene glycol monomethyl ether, and prepare 1.6 g of dimethylformamide solution of AIBN with a mass fraction of 5% as an initiator, and react at 90°C for 4 hours to obtain the adhesive for aramid fiber aerogel film.

[0042] The raw materials, dosage and preparation method for preparing the aramid fiber dispersion in this embodiment are as follows: first, weigh 10g of poly(p-phenylene terephthalamide) precursor, add 50g of deionized water to fully soak it, and then disperse it dropwise in 250g of deionized water under the action of a high-shear homogenizing and dispersing emulsifier, and disperse it for 5h to obtain an aramid fiber dispersion.

[0043] Then, 1.55 g of an adhesive for the aramid fiber aerogel film was added to 310 g of an aramid fiber dispersion, and then 8.4 g of 9.8% by mass dilute sulfuric acid was added and stirred for 10-15 min, and then 12 g of 5% by mass sodium hydroxide solution was added and stirred for 10-15 min. 50 g of the mixed dispersion was taken, filtered and placed in the freezer of a refrigerator for 8 hours, and then freeze-dried for 24 hours, and then thermally cross-linked in an oven at 100°C for 4 hours to obtain a modified aramid fiber aerogel film product.

[0044] The modified aramid fiber aerogel film product prepared above was cut into 10mm×50mm strips, and the strip thickness was measured using a vernier caliper, and its mass was measured using an analytical balance to calculate its density. The strips were then placed on an electronic universal testing machine for testing, and the tensile strength and elongation at break were recorded. The tensile strength and elongation at break were divided by the density to obtain the specific tensile strength (MPa·cm 3 / g) and specific elongation at break (%·cm 3 / g). Figure 2 The tensile strength of the sample is 0.951MPa, the elongation at break is 4.49%, and the specific tensile strength and specific elongation at break are 0.024MPa·cm 3 / g, 0.112%·cm3 / g. At the same density, its tensile strength and toughness are better than those of unmodified aramid fiber aerogel film.

[0045] Example 3

[0046] The raw materials, dosage and preparation method of the adhesive for preparing aramid fiber aerogel film in this embodiment are as follows: first, weigh 2.5 g of N-hydroxymethyl acrylamide, 0.8 g of N,N-dimethyl acrylamide, 4.12 g of methyl methacrylate, 2.5 g of N,N-diethylaminoethyl methacrylate, and 19.4 g of propylene glycol monomethyl ether, and prepare 1.6 g of dimethylformamide solution of AIBN with a mass fraction of 5% as an initiator, and react at 90°C for 4 hours to obtain the adhesive for aramid fiber aerogel film.

[0047] The raw materials, dosage and preparation method for preparing the aramid fiber dispersion in this embodiment are as follows: first, weigh 10g of poly(p-phenylene terephthalamide) precursor, add 50g of deionized water to fully soak it, and then disperse it dropwise in 250g of deionized water under the action of a high shear homogenizing and dispersing emulsifier, and disperse it for 4h to obtain an aramid fiber dispersion.

[0048] Then, 1.55 g of an adhesive for the aramid fiber aerogel film was added to 310 g of an aramid fiber dispersion, and then 8 g of 9.8% by mass dilute sulfuric acid was added and stirred for 10-15 min, and then 11.4 g of 5% by mass sodium hydroxide solution was added and stirred for 10-15 min. 50 g of the mixed dispersion was taken, filtered and placed in the freezer of a refrigerator for 8 hours, and then freeze-dried for 24 hours, and then thermally cross-linked in an oven at 100°C for 4 hours to obtain a modified aramid fiber aerogel film product.

[0049] The modified aramid fiber aerogel film product prepared above was cut into 10mm×50mm strips, and the strip thickness was measured using a vernier caliper, and its mass was measured using an analytical balance to calculate its density. The strips were then placed on an electronic universal testing machine for testing, and the tensile strength and elongation at break were recorded. The tensile strength and elongation at break were divided by the density to obtain the specific tensile strength (MPa·cm 3 / g) and specific elongation at break (%·cm 3 / g). Figure 1 The sample has a tensile strength of 0.978 MPa, an elongation at break of 3.62%, and specific tensile strength and specific elongation at break of 0.024 MPa·cm 3 / g, 0.088%·cm3 / g. At the same density, its tensile strength is better than that of the unmodified aramid fiber aerogel film, and its toughness is slightly better than that of the unmodified aramid fiber aerogel film.

[0050] Example 4

[0051] The raw materials, dosage and preparation method for preparing the aramid fiber dispersion in this comparative example are as follows: first, weigh 10g of poly(p-phenylene terephthalamide) precursor, add 50g of deionized water to fully soak it, and then disperse it dropwise in 250g of deionized water under the action of a high shear homogenizing and dispersing emulsifier, and disperse it for 4h to obtain an aramid fiber dispersion.

[0052] Then, 50 g of the aramid fiber dispersion was filtered and placed in a freezer for 8 hours, and then freeze-dried for 24 hours to obtain an aramid fiber aerogel film product.

[0053] The aramid fiber aerogel film product prepared above was cut into 10mm×50mm strips, and the strip thickness was measured using a vernier caliper, and its mass was measured using an analytical balance to calculate its density. The strips were then placed on an electronic universal testing machine for testing, and the tensile strength and elongation at break were recorded. The tensile strength and elongation at break were divided by the density to obtain the specific tensile strength (MPa·cm 3 / g) and specific elongation at break (%·cm 3 / g).

[0054] The evaluation of the aramid fiber aerogel films prepared in Examples 1 to 3 and Example 4 was performed according to the following method:

[0055] Tensile strength: The samples of Examples 1 to 3 and Example 4 were cut into 10 mm × 50 mm strips and placed on an electronic universal testing machine for testing.

[0056] Table 1 Performance results of aramid fiber aerogels in Examples 1 to 3 and Example 4

[0057]

[0058]

[0059] As can be seen from Table 1, the density of Example 4 without the addition of the aramid fiber aerogel film adhesive is 44 g / cm 3 , the tensile strength is 0.812MPa, the elongation at break is 3.86%, and the specific tensile strength and specific elongation at break are 0.018 and 0.087 respectively.

[0060] The raw material formula and weight ratio of the adhesive for the aramid fiber aerogel film in Example 1 are as follows: 3.2% N-hydroxymethyl acrylamide, 5.8% N,N-dimethyl acrylamide, 16.6% methyl methacrylate, 6.5% N,N-diethylaminoethyl methacrylate, 62.7% propylene glycol monomethyl ether, 4.9% dimethylformamide, 0.25% AIBN, and the solid content is 32.26%. The density of the modified aramid fiber aerogel film in Example 1 is 43g / cm 3 The tensile strength and elongation at break were 0.949 MPa and 4.1%, respectively, and the specific tensile strength and specific elongation at break were 0.022 and 0.095, respectively, which were increased by 22.22% and 14.94% compared with Comparative Example 1.

[0061] Compared with Example 1, Example 2 increases the weight of N-hydroxymethyl acrylamide in the raw material formula of the adhesive for the aramid fiber aerogel film from 3.2% to 6.4%, and the density is 40g / cm 3 The tensile strength and elongation at break were 0.951 MPa and 4.49%, respectively, and the specific tensile strength and specific elongation at break were 0.024 and 0.112, respectively, which were increased by 33.33% and 28.74% compared with Example 4.

[0062] Compared with Example 1, Example 3 increases the weight of N-hydroxymethyl acrylamide in the raw material formula of the adhesive for the aramid fiber aerogel film from 3.2% to 8.1%, and the density is 41g / cm 3The tensile strength and elongation at break were 0.987 MPa and 3.62%, respectively, and the specific tensile strength and specific elongation at break were 0.024 and 0.088, respectively, which were increased by 33.33% and 1.15% compared with Example 4.

[0063] With the increase of the weight of N-hydroxymethyl acrylamide in the raw materials, the specific tensile strength of the modified aramid fiber aerogel film increases all the time, while the specific elongation at break increases first and then decreases.

[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. Adhesive resin, characterized in that: The chemical structural formula of the adhesive resin is as follows: Wherein x is the degree of polymerization of N,N-dimethylacrylamide of 31-78, y is the degree of polymerization of methyl methacrylate of 28-149, z is the degree of polymerization of N,N-diethylaminoethyl methacrylate of 68-179, and m is the degree of polymerization of N-hydroxymethylacrylamide of 53-155.

2. The adhesive resin according to claim 1, characterized in that: The molecular weight of the adhesive resin is 30,000-70,000.

3. The adhesive resin according to claim 2, characterized in that: The molecular weight of the adhesive resin is preferably 40,000-50,000.

4. The adhesive resin according to any one of claims 1 to 3, characterized in that: The adhesive resin is formulated in the following proportions by mass: 3.2% to 8.1% N-hydroxymethyl acrylamide, 2.5% to 5.8% N,N-dimethyl acrylamide, 13.3% to 16.6% methyl methacrylate, 6.5% to 8.1% N,N-diethylaminoethyl methacrylate, 62.7% propylene glycol monomethyl ether, 4.9% N,N-dimethylformamide, and 0.25% azobisisovaleronitrile (AIBN), with a solid content of 32.26%.

5. The method for preparing the adhesive resin is characterized in that: The steps are as follows: S1: Raw material preparation: N-hydroxymethyl acrylamide 3.2%-8.1%, N,N-dimethyl acrylamide 2.5%-5.8%, methyl methacrylate 13.3%-16.6%, N,N-diethylaminoethyl methacrylate 6.5%-8.1%, S2: AIBN was used as the initiator and prepared into a 5% N,N-dimethylformamide solution. S3: adding the raw materials in step S1 and the initiator solution in step 2 into a reactor containing a solvent in four times at intervals of 10 to 15 minutes, with a reaction temperature of 70-90°C, a reaction time of 5-10 hours, a stirring speed of 300 rpm to 450 rpm, and obtaining the adhesive resin by solution free radical polymerization.

6. The method for preparing the adhesive resin according to claim 5, characterized in that: The solvent is a mixed solution of propylene glycol monomethyl ether and N,N-dimethylformamide, and the composition formula of the solvent solution is as follows: 46.4% to 92.7% of propylene glycol monomethyl ether and 7.3% to 53.6% of dimethylformamide in weight percentage.

7. A modified aramid fiber aerogel film prepared using the adhesive resin according to claim 6.

8. The method for preparing the modified aramid fiber aerogel film according to claim 7, characterized in that: The adhesive resin is directly added to the aramid fiber dispersion at 15.5% of the mass of the aramid fiber, and then diluted hydrochloric acid or diluted sulfuric acid is added and stirred for 10-15 minutes to fully dissolve the polymer, and then sodium carbonate solution or sodium hydroxide solution is added to neutralize the acid, and the polymer is uniformly precipitated, and after being filtered and frozen for 8 hours, and then freeze-dried for 24 hours, it is thermally cross-linked in an oven at 100°C for 4 hours to obtain the modified aramid fiber aerogel film.

Citation Information

Patent Citations

  • Aramid nanofiber-based composite aerogel and preparation method thereof

    CN113278191A

  • Poly-p-phenylene terephthamide (PPTA) aerogel and preparation method thereof

    CN116102774A

  • Copolymer cross-linking agent applied to antifogging coating and preparation method of copolymer cross-linking agent

    CN117801154A

  • Adhesive composition

    JP1987100569A

  • Methacrylate oligomers for adhesive compounds

    WO2019185377A1